Obstructive sleep apnea syndrome and parodontium in children - DJOSSOU, MEDESSÈ DAVID (My University, 2017)
ABSTRACT Obstructive Sleep Apnea Syndrome (OSAS) in children is characterized by a prolonged partial obstruction of the upper airway or a complete and intermittent obstruction, which disturbs the ventilation during sleep and / or its normal course. Its prevalence in children is 1 to 4% in the general population and 30 to 50% of these children present a gingival inflammation. The objective of this work is to highlight a possible link between these two pathologies by a review of literature. We consulted the Cochrane, PubMed and Scopus databases. Only article studying the link between OSA and periodontal health in children confirms this. Children in the study group (with SAOS) had fewer cavities, plaque, gingival inflammation and better hygiene. The link between OSAS and periodontal health in children could not be demonstrated by that review of literature. The bibliographic study allowed us to proof show that the symptomatology of OSAS (oral ventilation, xerostomia) is related to the gingival inflammatory factor.
Keywords: Obstructive apnea; periodontal; children.